User Experience Design Development of the Siakad UNY Mobile Application Using the Design Thinking Method - Alawdi, Yhogi; Eko Marpanaji; Rahmatul Irfan (International journal of technology and education research, 2025)
This study aims to develop and evaluate the mobile-based Academic Information System application of Yogyakarta State University to enhance the quality of student user experience in accessing academic services. The application was developed to provide academic service solutions that better align with user needs, particularly for smartphone usage. This research employed a Research and Development method using a Design Thinking approach, encompassing the stages of empathize, define, ideate, prototype, and test. The study was conducted at Yogyakarta State University involving 35 active students from various study programs as end users. Data were collected using the User Experience Questionnaire (UEQ) distributed online via Google Forms. The UEQ instrument demonstrated good reliability, with all dimensions achieving Cronbach’s Alpha values above 0.7. Data analysis was performed using the UEQ Data Analysis Tool to obtain mean scores and user experience quality categories based on the UEQ Benchmark. The results indicate that the Siakad UNY mobile application achieved an Excellent rating in attractiveness, efficiency, stimulation, and novelty, and a Good rating in perspicuity and dependability. These findings suggest that the application provides a high-quality user experience and is suitable as a mobile-based academic service solution. Further development is recommended to enhance clarity and system reliability to optimize user experience quality.